A senses-based model for experiential tourism - Luca Meacci; Giovanni Liberatore (Tourism & Management Studies, 2018)
An experience can be defined as anything that stimulates the senses, heart and mind. Senses play a central role in individuals’ perceptions of the surrounding world. Thus, research on tourist experiences’ sensory dimensions is pivotal to improving visitor management in tourism. Recent studies have shown that successful tourism destinations attract tourists using a systematic approach to stimulating all the senses. This paper discusses the case of a multisensory criteria model applied to the tourism destination of Fiesole, Italy. The main aim was to provide a critical analysis of the various steps and outcomes of tourism experience design. The findings include a set of key tourism-related sensory experience concepts and the critical importance of following a logical order in experience processes. The results provided a theoretical framework that served as the foundation of a senses-based model, which not only provides an innovative focus within tourism research but also can function as a user-friendly tool for operators who need to plan, monitor and evaluate tourist experiences.